Javanese Language and Culture in the Expression of Kebo Bule in Surakarta: An Ethnolinguistic Study - Abdullah, Wakit - (KOMUNITAS: INTERNATIONAL JOURNAL OF INDONESIAN SOCIETY AND CULTURE, 2016)
The phenomenon of Kebo Bule as the actuality of Javanese language and culture in Surakarta can be criticized from the perspective of ethnolinguistic. In terms of the descriptive qualitative expression of the language and culture of Java, Kebo Bule from the perspective of Ethnolinguistic is identifiable on the background of it in Surakarta, the influence of Kebo Bule to the Surakartaâs Court, and the meaning of Kebo Bule as one of the magical icons of the Surakartaâs Court. Ethnolinguistic as a theoretical concept is part of the branch of linguistic studies that seeks to study the language understanding in a broader context in order to express an understanding of the culture. Methodologically, understanding the relationship between the expression of language and culture Kebo Bule can be peeled using ethnomethodology to ethnolinguistics by utilizing ethnoscience (knowledge typically owned by ethnicity, tribe, people) to find the cultural themes of people related to their mindset and the worldview. The research data encompasses of oral and written data, verbal data sources from informants and writes from a library. The validity of the data was done by triangulation, and data analysis using ethnoscience (especially taxonomic, domain and componential analysis). Results of the discussion is presented in the form of narrative texts related to the background, the effect and meaning Kebo Bule for the existence of the language and culture of Java in Surakarta.